Effect of the Essential Oil of Clausena anisata (Rutaceae) and Palm Kernel Vegetable Oil on Engorged Females of Three Species of Ixodidae Cattle Ticks - Eyabana, Mollong; Yaovi, Nuto; Akpéni, Bawa Rabiétou; Boris, Kasseney Dodji Boris; Mondjonnesso, Gomina; Panawé, Tozoou (European Scientific Journal, ESJ, 2018)
Improving and increasing livestock production system yield requires parasite control, especially ticks, which stifle the emergence of successful breeding units. Effective environmentally friendly and biological parasite control is urgently required. The purpose of this study was to evaluate the effects of the essential oil of Clausena anisata (Rutaceae) and of palm kernel vegetable oil compared to a reference chemical acaricide, flumethrin, on the biological parameters of the engorged females of three major tick species in the Maritime Region of Togo. The topical tests applied consisted respectively of depositing a drop of 75μL and 5μL of the crude extracts and their dilutions on the back of each female of Amblyomma variegatum, Rhipicephalus (Boophilus) decoloratus, and Rhipicephalus (Boophilus) microplus (Ixodida: Ixodidae). Fifteen females and three replicates were tested, incubated at 28 ± 1°C, 85-95% RH, 12: 12 L:D, and were monitored daily. C. anisata caused 100% mortality in all engorged females and its 1/8 dilution destroyed 100% of eggs laid by A. variegatum. Palm kernel vegetable oil caused 100% mortality in female species of the genus Rhipicephalus (B.). Flumethrin was very toxic to ticks. Since Palm kernel vegetable oil has a significant toxicity, the two oils tested can be an alternative control of the studied ticks after additional studies.